2014
DOI: 10.1088/1054-660x/24/11/115106
|View full text |Cite
|
Sign up to set email alerts
|

A phase-sensitive optical time-domain reflectometer with dual-pulse phase modulated probe signal

Abstract: A novel configuration of a phase-sensitive optical time-domain reflectometer (OTDR) utilizing dual-pulse phase modulations of the probe signal is presented and experimentally demonstrated. The proposed modulation method enables one to perform the demodulation and reconstruction of an external perturbation signal which impacts the fiber using the phase diversity technique. The proposed phase-sensitive OTDR has some advantages in comparison with conventional solutions, which are discussed. The feasibility of a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 9 publications
0
80
0
Order By: Relevance
“…This concept was later adopted and modified by Lewis and Russell 16,17 DVS capable of measuring the vibrations along the sensing fibre. In 2014, Alekseev et al 18 experimentally demonstrated this concept by controlling the relative phase of a dualpulse probe signal. The experimental results showed that this sensing technique is capable of measuring 230 Hz periodic perturbations along a 2 km long sensing fibre with a spatial resolution of 5 m and a phase sensitivity of 0.01 rad.…”
Section: A Optical Time Domain Reflectometry (Otdr)mentioning
confidence: 99%
“…This concept was later adopted and modified by Lewis and Russell 16,17 DVS capable of measuring the vibrations along the sensing fibre. In 2014, Alekseev et al 18 experimentally demonstrated this concept by controlling the relative phase of a dualpulse probe signal. The experimental results showed that this sensing technique is capable of measuring 230 Hz periodic perturbations along a 2 km long sensing fibre with a spatial resolution of 5 m and a phase sensitivity of 0.01 rad.…”
Section: A Optical Time Domain Reflectometry (Otdr)mentioning
confidence: 99%
“…However, a more precise quantitative measurement of an external disturbance requires additional information on the change in signal behavior induced by strain or temperature changes. To this end, techniques which are based on frequency shift measurements [36][37][38][39] and others using direct demodulation of the phase change [35,[40][41][42][43][44] have been proposed. The frequency shift method for external impact extraction using ϕ-OTDR is based on the observation that the frequency of the probing pulses can be matched with a corresponding change in temperature or strain with some proportionality constant.…”
Section: ϕ-Otdr Sensors For Precise Impact Extraction Using Frequencymentioning
confidence: 99%
“…A ϕ-OTDR sensor, which emulates the 3 × 3 coupler used in [40,41] and resolves the receiver multiplicity and synchronization issues by making alternate use of a single photodiode and addressing drawbacks of interferometric stability with the use of a double-pulse scheme, has also been proposed [42]. The modulation of the pulses and the operating principle of the configuration is depicted in Figure 13.…”
Section: ϕ-Otdr Sensors For Precise Impact Extraction Using Frequencymentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014, Alekseev et al (Alekseev 2014) experimentally demonstrated a modified version of this concept by using a semiconductor optical amplifier to generate 100ns pulses while controlling the relative phase of pulse pair using an electro-optic modulator (EOM).…”
Section: Figure 2 the Experimental Setups Of Three Dvs The Operationmentioning
confidence: 99%